Evaluation of Short-term Precision for Tibial Ultrasonometry - Lequin, M. H.; van Rijn, R. R.; Robben, S. G. F.; Hop, W. C. J.; Dijkhuis, S.; Fijten, M. M. E. G.; Meijer, L. A. W.; van Kuijk, C. (Calcified tissue international, 1999)
Tibial quantitative ultrasonometry is a relatively novel technique in the field of bone sonometry, an emerging alternative to bone densitometry. The implementation of this technique in a pediatric population could prove valuable from a clinical as well as a research viewpoint. In clinical practice it is necessary to know the precision of this technique and the possible influence on measurements before implementation. This study presents the precision in a Caucasian pediatric population and the influence of measurement site, dexterity, brand of coupling gel, and temperature of coupling gel. To assess intra- and interobserver variance duplicate measurements, with repositioning, ultrasonometry was performed in 10 children over a short period of time. The observers were blinded for the results of the other observer and after each measurement the skin markings were removed. Intraobserver variance for operator one (MHL) and for observer two (SFGR) was CV 0.43%. The interobserver variance was CV 0.61%. Left midtibial and right midtibial speed of sound (SOS) measurements showed no significant differences. There were, however, significant differences in both boys and girls between right proximal versus right midtibial, right midtibial versus right distal, and right proximal versus right distal (for all P < 0.001). One-way analysis of variance (ANOVA) showed that neither the use of different coupling gels nor an increase in gel temperature had a significant influence on measurements. The results of our study show that tibial quantitative ultrasonography (QUS) is a highly reproducible technique in a Caucasian pediatric population.